The Role Of Virtual Health Coaching In Improving The Quality Of Life Among Patients With Hypertension In Jeddah Community (The Review of Diabetic Studies, 2026)
Background: Hypertension is a significant public health problem in Saudi Arabia that has affected 20.7% of the population. Undertreated hypertension patients face severe, potentially deadly health complications, including cardiovascular disease and stroke. In Saudi Arabia, increasing demand for primary care has made it challenging for patients with hypertension to obtain conventional primary care services. Virtual health coaching clinics are a recent innovation in Saudi Arabia that help patients with chronic diseases make lifestyle changes to reduce their risk of complications.Aim: To evaluate the effect of virtual health coaching on the Quality of Life of patients with hypertension in the Jeddah community.Methods: A cross-sectional quantitative research method was used. Adult patients with hypertension in the Jeddah city community completed an online survey comprising a sociodemographic form and the Arabic version of the 36 Item Short Form Survey, which measures Quality of Life. Descriptive and correlational analyses were performed to evaluate the Quality of Life and health-related outcomes. Results: Ninety-five patients participated in this study. Female patients, under 40 years of age, unmarried, and with higher education levels reported better general health and physical functioning. In addition, the frequency of clinic sessions was positively associated with improvements in physical and mental health. A substantial positive correlation was observed between vitality and mental health. As well as between social functioning and emotional role.Conclusion: This study highlights the essential need for continuous support and guidance to achieve a high Quality of Life by delivering individualized assistance, promoting sustainable behavioral changes, and enhancing patient involvement.Recommendations: Clinicians should incorporate digital health training in remote monitoring and chronic disease management. Policymakers must implement legislation, allocate resources to telemedicine, guarantee reimbursement, and enhance visibility. Addressing these patient-related areas will improve health outcomes and facilitate sustained hypertension management.